Category 6 day of destruction - Lowry, Dick; Sutter, Randy; Belzberg, Leslie; Dorff, Matt (Los Angeles, CA : Hallmark Entertainment, 2004)
Fictional account of a national crisis in the form of three disasterous weather systems
Title from container
Executive producers, Robert M. Sertner, Frank Von Zerneck
Cast: Thomas Gibson, Nancy McKeon, Randy Quaid, Junko Bailey, Chandra West, Brian Markinson, Nancy Sakovich
DVD Format, English Dolby digital 5.1 and 2.0
With English and Chinese subtitles
Keywords: Natural disasters -- Drama; Television mini-series